Ben Cao Gang Mu. Volume VI, Vegetables, Fruits - Li, Shizhen (Berkeley : University of California Press, 2024)
Volume VI in the Ben cao gang mu series offers a complete translation of chapters 26 through 33, devoted to vegetables and fruits. The Ben cao gang mu is a sixteenth-century Chinese encyclopedia of medical matter and natural history by Li Shizhen (1518-1593). The culmination of a sixteen-hundred-year history of Chinese medical and pharmaceutical literature, it is considered the most important and comprehensive book ever.
5.4 Measures of the Size of Pills -- 6. Lists of Substances -- 6.1 Identification of Pharmaceutical Substances of Plant Origin Mentioned in BCGM ch. 26 -- 33 in Passing. Herbs with an Entry of their Own are Marked with their Entry Number -- 6.2 Substances Discussed in Chapters 26 -- 33 in a Separate Entry. Listed in Alphabetical Order of their Proper Pin Yin Names with their Popular English Names and References to their Entry.
Description based upon print version of record.
6.3 Currently Accepted Scientific Identification of Substances Discussed in BCGM ch. 26-33 in a Separate Entry. Listed in Alphabetical Order, with Reference to their Entry.
Description based on online resource; title from digital title page (viewed on February 22, 2024).
JSTOR
Keywords: Materia medica -- China -- Early works to 1800.; Medicine, Chinese -- Early works to 1800.; Natural history -- China -- Pre-Linnean works; Medicine, Chinese -- Herbal; Matière médicale -- Chine -- Ouvrages avant 1800.; Médecine chinoise -- Ouvrages avant 1800.; Sciences naturelles -- Chine -- Ouvrages prélinnéens.; MEDICAL / Acupuncture; Materia medica; Medicine, Chinese; Natural history; China; Early works